2019
DOI: 10.30525/2256-0742/2018-4-5-75-81
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency in the System of Money Laundering

Abstract: The target of the article is to study the place of the cryptocurrency in the process of money laundering. The subject of the article is to investigate the ways and means of usage cryptocurrency for money laundering, the possibilities, and limits. Problem’s setting. The authors of the paper have emphasized that despite the broad usage of cryptocurrency all over the world for different kinds of purchasing and transactions, there is no unified position regarding the definition of cryptocurrency, as well as its le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 5 publications
(5 reference statements)
0
28
0
Order By: Relevance
“…A cryptocurrency user can have more than one account and perform transactions from different locations at the same time. Contrary to the above views [10], other findings of [11] show that cryptocurrencies do not behave like traditional currencies or commodities and represent a sector that is much more advanced and less speculative.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…A cryptocurrency user can have more than one account and perform transactions from different locations at the same time. Contrary to the above views [10], other findings of [11] show that cryptocurrencies do not behave like traditional currencies or commodities and represent a sector that is much more advanced and less speculative.…”
Section: Introductionmentioning
confidence: 65%
“…Cryptocurrencies involved in the money laundering process is dealt with by [10]. The results of the study showed that cryptocurrency is a suitable tool for money laundering because it provides the currency owner with relative anonymity because it does not require any personal information about the user and his location.…”
Section: Introductionmentioning
confidence: 99%
“…Bitcoin allows for various money laundering schemes, which virtually blocks the possibility of identifying criminals. The mentioned characteristics of the cryptocurrency encourage legislators around the world to unify the legal system for the use of cryptocurrency as a means of payment [8].…”
Section: Resultsmentioning
confidence: 99%
“…The recorded prices in the dataset were collected on a daily basis from 1 January 2018 to 30 June 2021. In this research, we used time-series data from [19] with 1277 records. Table 1 illustrates the dataset specification of the targeted cryptocurrency and Figure 10 shows sample data from the dataset.…”
Section: Datasetmentioning
confidence: 99%
“…There is evidence that the usefulness of different information sets varies between machine learning algorithms, implying that prediction is likely to be much more complicated when a set of machine learning algorithms is used [18]. Despite the widespread use of cryptocurrencies for various types of purchases and transactions around the world, there is no consistent opinion on the definition of cryptocurrency or its legal status [19]. Furthermore, the aforementioned situation exacerbates challenges in criminal investigations of cryptocurrency-based money laundering.…”
Section: Introductionmentioning
confidence: 99%